A systematic review of nanocarriers used in medicine and beyond — definition and categorization framework - Sabine Gressler; Christina Hipfinger; Florian Part; Anna Pavlicek; Christian Zafiu; Bernd Giese (Journal of Nanobiotechnology)
Abstract Nanocarriers are transport and encapsulation systems that primarily serve to protect and improve the dispersibility of predominantly hydrophobic active ingredients but also enable their targeted delivery and controlled release at the site of action. Nanocarriers are mainly made of either organic or inorganic materials, but various combinations of materials in complex structures are also under development. Most nanocarriers represent entities that are rationally designed to meet the functional requirements of a specific application. They can therefore be understood as Advanced Materials. Nanocarrier systems are already being used in medicine, cosmetics, agriculture, food, and household products. They are therefore used in a variety of products, ideally designed to be safe and sustainable, and may need to be registered before they can be placed on the market. Inspired by medical research, nanocarriers are also increasingly being used for precision farming (nano-agrochemicals) or products, such as air fresheners or lithium-ion batteries, and could thus be released into the environment in large quantities. To enable the identification of critical nanocarriers in subsequent investigations, a comprehensive literature review of the broad and heterogeneous research field of nanocarriers is provided, as well as an approach for categorization based on the origin and chemical composition of their constituent materials. A definition of nanocarriers based on size (1–1000 nm) and function is also proposed for their risk assessment.